Mucoid Degeneration of the Anterior Cruciate Ligament: Characterization of Natural History, Femoral Notch Width Index, and Patient Reported Outcome Measures - Hotchen, Andrew J.; Demetriou, Charis; Edwards, Dennis; Melton, Joel T. K. (The Journal of Knee Surgery, 2019)
The presentation and clinical course of mucoid degeneration of the anterior cruciate ligament (MD-ACL) are poorly documented within the literature. Subsequently, it is under-diagnosed and the optimal management strategy remains ill-defined. Here, we characterize the syndrome associated with MD-ACL and compare the natural clinical course with the outcomes of arthroscopic management. Thirty-one patients with radiological features of MD-ACL over a 2-year period had their clinical notes retrospectively reviewed. Seven patients underwent arthroscopic debridement of the ACL for MD. These were followed up for a minimum of 2 years and an average of 2.8 years from surgery. The remainder were managed conservatively (n = 24) and were followed up for a minimum of 2 years and an average of 4.0 years. The notch width index (NWI) and associated pathology was noted. Primary outcome measures were presence of knee pain and use of analgesia. Secondary outcome measures were the Oxford and Lysholm knee scores. The most commonly reported symptoms were posterior knee pain (77.4%) and limitation of terminal flexion (58.1%). All patients who underwent arthroscopic debridement were pain and analgesia free at follow-up. Of the patients who did not undergo arthroscopic surgery, three patients had knee replacement surgery and three were lost to follow-up. The remaining patients, 14/18 (77.8%), reported knee pain and regular analgesia use at follow-up, which was significantly more than the arthroscopic debridement group (p < 0.01). The knee scores were significantly better in the arthroscopic debridement group at follow-up (Oxford knee score: 45 vs 34; Lysholm: 92 vs 67; p < 0.01). Furthermore, the postoperative improvement in the Oxford knee and Lysholm scores compared with preoperatively was 12.1 and 31.8 points, respectively (p < 0.01). The NWI was increased in patients with mild-to-severe osteoarthritis (0.266 vs 0.273; p < 0.05). MD-ACL should be considered in patients who report posterior knee pain, limitation of terminal flexion, and it can be associated with other knee pathologies. MD-ACL can be successfully managed with arthroscopic radio frequency debulking with improvement in quality of life at follow-up.
Keywords: celery stalk; mucoid degeneration; anterior cruciate ligament